Effect of variable valve timing (VVT) on engine performance - 464515 Tan, Ching Siong (Skudai : Universiti Teknologi Malaysia, 2003)
Projek Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2003